Facebook addiction and depression in adults [19 years-64 years] - Norman, Prasan; Elavarasan, Karthikeyan; Dhandapani, Thirunaaukarasu (International Journal Of Community Medicine And Public Health, 2017)
Background: Face book, one of the most popular social networking sites, has been a popular time pass activity site. Most of the users log in at least once daily. Some even keep their Facebook accounts online over their mobile phones/android devices throughout the day. Most studies take into account the association of social networking sites and depression in adolescents or school students/college students etc. Hence this study was conducted in adults aged 19years to 64 years. Methods: A study was conducted to determine Facebook addiction and depression in those users aged 19 years to 64 years in India from April 1st 2016 to April 1st 2017. The participants were interviewed through an online questionnaire. Results: This study was conducted among four hundred and sixty nine adults of age nineteen years to sixty four years of which Two hundred and fifty three were males and two hundred and sixteen were females. 64% of the participants were addicted to Facebook. 40.66% (122) had signs of depression. Conclusions: Simple measures like spending time with friends and loved ones, going out for a ride, attending social gatherings, doing activities that release endorphins and decreasing the time spent on social networking sites could help prevent Facebook addiction and depression.